A randomised cross-over cohort study of exposure to emissions from a road tunnel ventilation stack. Issue 4 (17th August 2012) - Cowie, Christine T; Ezz, Wafaa; Xuan, Wei; Lilley, William; Rose, Nectarios; Rae, Michael; Marks, Guy B
Abstract : Background and objective: Road tunnels are increasingly important components of urban infrastructure. However, knowledge of their health impact on surrounding communities is limited. Our objective was to estimate the short-term respiratory health effects of exposure to emissions from a road tunnel ventilation stack. Methods: We conducted a randomised cross-over cohort study in 36 volunteers who underwent three exposure scenarios in 2006 before the road tunnel opened, and in 2007 (n=27) and 2008 (n=20) after the tunnel opened. Exposure downwind of the stack was compared to upwind of the stack and to a distant heavily trafficked location adjacent to a main road. Spirometry, exhaled nitric oxide (eNO) and symptom scores were measured repeatedly during each 2 h exposure session. Results: Downwind locations were associated with increased reports of 'dry nose' (score difference 0.36; 95% CI 0.09 to 0.63) compared with the control location (2006 vs 2007/2008), but not with impaired lung function, increased airway inflammation or other symptoms. The heavily trafficked location was associated with significantly increased eNO (ratio=1.09; 95% CI 1.04 to 1.14), eye (score difference 0.05; 95% CI 0.01 to 0.10) and chest (score difference 0.21; 95% CI 0.09 to 0.33) symptoms compared to the stack locations. Conclusions: There was no consistent evidence of adverse respiratory effects from short-term exposures downwind of the tunnel ventilation stack, except for dry nose symptoms. However, the findings of increased airway inflammation and symptoms in subjects after only 2 h exposure at the heavily trafficked location, are suggestive of detrimental effects of short-term exposures to traffic-related air pollution.